2015
DOI: 10.1136/bjophthalmol-2014-306051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posterior vitreous detachment on aqueous humour levels of VEGF and inflammatory cytokines

Abstract: PVD is related to the change in the multiple intraocular inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It has been shown that intraocular cytokine concentration may change after intravitreal injection if a posterior vitreous detachment occurs 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that intraocular cytokine concentration may change after intravitreal injection if a posterior vitreous detachment occurs 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Posterior vitreous detachment (PVD) was examined by B-mode ultrasonography (UD-6000), as previously detailed elsewhere. 13 14 Briefly, the mobility of the posterior vitreous during ocular saccades was examined using the ‘through the lid contact’ technique. If the posterior vitreous was detached from the retinal surface and motile with eye movements, the eyes were categorised as having complete PVD (PVD group); otherwise, the eyes were categorised as the without PVD group.…”
Section: Methodsmentioning
confidence: 99%
“…For the measurement of axial length, A-mode ultrasonography (UD-6000; Tomey Corp., Aichi, Japan) was used. B-mode ultrasonography (UD-6000) was used To examine posterior vitreous detachment (PVD), as previously described [16][17][18][19][20][21], and the eyes were either categorised into the PVD group or the without PVD group.…”
Section: Clinical Examinationsmentioning
confidence: 99%
“…Further studies including the balance of extracellular matrix remodelling factors such as TIMP/MMP [53] are required to understand how low concentrations of MMP-9 are associated with the number of injections. CXCL12 is a chemotactic factor for lymphocytes and promotes angiogenesis [54,55]. Interestingly, bone marrow-derived cells distributed in a mouse laserinduced CNV model are CXCL12 receptor-positive [56].…”
Section: Number Of Injections and Cytokinesmentioning
confidence: 99%